2013
DOI: 10.4028/www.scientific.net/amr.864-867.861
|View full text |Cite
|
Sign up to set email alerts
|

Contents and Characteristics of Phthalic Acid Esters in Municipal Sewage Sludge in Jiangsu Province

Abstract: Concentrations of 6 kinds of phthalic acid esters (PAEs) in sewage sludge from 20 typical municipal wastewater treatment plants (WWTPs) in Jiangsu province were determined by gas chromatography-mass spectrometry (GC-MS) . The results shows that the sewage sludge samples contain phthalic acid ester compounds, which total content of phthalic acid esters ( PAEs) range from 15.126 to 71.107 ug/g (dry sludge). The content of diethylhexyl phthalate (DEHP) is the highest, which amounts more than 80% of total phthalic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…The application of composted manure adds extraneous dissolved organic matter (DOM) to the soil, and DOM enhances the adsorption capacity of DBP by soils through partitioning (Wu et al, 2018). Organic fertilizers, manures, composts, and biowaste fermentation (anaerobic digestate) Fang Wang et al are all known sources of MPs and PAEs in the environment; 16 PAEs were identified in sludge from Shanghai ranging from 22.6 to 1350 mg PAEs kg -1 sludge (dry weight) (Zhao et al, 2014). MP content was up to 41 particles g -1 in sludge from fields that underwent sludge applications (Corradini et al, 2019).…”
Section: Fertilisers Compost and Sludgementioning
confidence: 99%
“…The application of composted manure adds extraneous dissolved organic matter (DOM) to the soil, and DOM enhances the adsorption capacity of DBP by soils through partitioning (Wu et al, 2018). Organic fertilizers, manures, composts, and biowaste fermentation (anaerobic digestate) Fang Wang et al are all known sources of MPs and PAEs in the environment; 16 PAEs were identified in sludge from Shanghai ranging from 22.6 to 1350 mg PAEs kg -1 sludge (dry weight) (Zhao et al, 2014). MP content was up to 41 particles g -1 in sludge from fields that underwent sludge applications (Corradini et al, 2019).…”
Section: Fertilisers Compost and Sludgementioning
confidence: 99%